Dampak Status Penguasaan Lahan terhadap Pendapatan Usahatani Padi di Desa Tambakmerang Kecamatan Girimarto: Impact of Land Tenure Status on the income of rice farming in Tambakmerang Village, Girimarto District - Yulianawati Yulianawati; Tria Rosana Dewi; Umi Nur Solikah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
The purpose of this research is (1) to analyze the income level of rice farming in the farmer-owners, tenants, and Husbandmen at Tambakmerang Village Girimarto District. 2 to analyze the efficiency of rice farming in the farmers, tenants, and Husbandmen in Tambakmerang village Girimarto subdistrict. This study was implemented using the method of detailed analysis with disproportionate sampling in random sampling. The methods of analysis used in this research are revenue analysis and efficiency analysis. The results of the research concluded that the level of income of rice farming in the farm owner of the Pengrake, renter, and Husbandmen in the village of Tambakmerang Girimarto District Wonogiri is for farmers owners of the tenants amounting to Rp. 38,239,416.7, the tenant farmers amounting to Rp. 20,153,625 and farmer of a Pengrake Rp. 18,762,662.50. The efficiency of rice farming in the farmer's owner, tenants, and Husbandmen at Tambakmerang Village Girimarto District Wonogiri Regency is for the owner of a pengrake 4.34, the tenant farmer of 2.87 and farmer of the husbandmen of 2.52. This suggests that rice farming in the area of research has been finalized and can still be improved.